Energy Effectiveness Strategic Objectives, Energy and Water at the Heart of Enterprise - McCardell, Sandra (Springer International Publishing, 2018)
This book describes practical ways to understand energy and water use in organizations and then manage or control that use, thereby reducing risk and cost. The author presents a strategic framework to focus on the types of questions that should be addressed internally, Including evaluation of potential projects, planning and implementing energy projects, and evaluating results. The premise is that no modern organization can exist without energy, despite the fact that energy is also one of the mandatory inputs that receives little to no attention in most organizations. This work highlights methodologies and projects that illuminate ways in which energy management is central to an organization's success, considering in each case the four main determinants of energy use: People, Buildings, Equipment /Processes, and the Environment. The book constitutes a complete energy savings resource for business owners, middle managers, and building and energy managers, providing options, free tools, and flexible project templates.